Stability, spontaneous and induced polarization in monolayer MoC, WC, WS, and WSe. (13th December 2018) - Samad, Abdus; Kim, Hye Jung; Shin, Young-Han
Abstract: Ferroelectricity in the ultra-low thin films of the ferroelectric materials is a rare phenomenon due to the depolarization electric field established by the uncompensated surface charge. Using density functional theory based calculations, we design buckled honeycomb binary monolayer MoC, WC, WS, and WSe. The feasibility of their experimental synthesis is evident from their low formation energies, stable lattice vibrations, and high elastic stiffnesses. The difference in electronegativity of the building atoms and lack of inversion symmetry results in high spontaneous out-of-plane polarization whereas all the in-plane components cancel out. The existence of the mirror plane along the armchair direction vanishes the in-plane piezoelectric stress effects for a strain applied along the zigzag direction. However, a strain along the armchair direction on MoC and WC results in a high piezoelectric coefficient up to 10 10 C m, about three times larger than that reported for monolayer MoS . The polarization switching barriers for the out-of-plane components range from 0.55 to 2.70 eV per formula unit.